UPAYA MENINGKATKAN MOTIVASI BELAJAR BIOLOGI MATERI TEORI EVOLUSI DENGAN METODE PEMBELAJARAN PENEMUAN (DISCOVERY LEARNING) PADA SISWA KELAS XII IPA1 DI SMA NEGERI 6 KOTA BEKASI - Lucia Christyanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2015)
This Classroom Action Research was conducted because of the low learning motivation and learning achievements of students in the subjects of Biology and still has not done well the use of learning methods, especially in the learning process in the Biology class of XII IPA 1 SMAN 6 Bekasi. This research outputs indicated that Discovery Learning has a positive impact in improving students' motivation. Based on data analysis, the activity of the teacher in the learning process using Discovery Learning method in each cycle also increased as well as the positive impact on student achievement. This can be shown by the average value of students in each cycle which is constantly increasing. Thus the hypothesis of action in this study proved that the application of the discovery learning method (Discovery Learning) in teaching and learning can enhance students' motivation to learn Biology with the material theory of evolution.Keywords : Motivation, Achievement, Biology, Evolution, Discovery Learning Method